Istilah “Kalimat” Dalam Sintaksis Bahasa Arab Dan Bahasa Sunda - Rizan Zulfikri; Yuyun Rohmatul Uyuni; Ubaidillah Ubaidillah (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
The study was conducted to obtain the concept and comparison of the term "sentence" in Arabic and Sundanese. The term "sentence" in Sundanese, although it is an upturned word from Arabic, has a different meaning due to a change in meaning itself. On the other hand, almost all of the Nahwu book begins with a discussion related to the term "sentence", this indicates that the Nahwu science scholars have paid special attention to the urgency of "sentence" in Arabic Syntax. The term "Sentence" in Arabic means singular (Mufrad) means it is not composed of units which have meaning if separated, while in Sundanese the definition is a grammatical construction meaning consisting of units and is predicative. These differences require a bridge to be able to make interpretations and get the correct understanding. Through literature study, as well as descriptive analysis and translational equivalents, the concept of sentences in the syntax of the two languages ​​will be explained, then the matching of terms is carried out in each language to obtain an objective concept.